2011
DOI: 10.1021/nl201514a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineering the Heart: Conductive Scaffolds Enhance Connexin 43 Expression

Abstract: Scaffolds that couple electrical and elastic properties may be valuable for cardiac cell function. However, existing conductive materials do not mimic physiological properties. We prepared and characterized a tunable, hybrid hydrogel scaffold based on Au nanoparticles homogeneously synthesized throughout a polymer templated gel. Conductive gels had Young's moduli more similar to myocardium relative to polyaniline and polypyrrole, by 1-4 orders of magnitude. Neonatal rat cardiomyocytes exhibited increased expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
219
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(230 citation statements)
references
References 65 publications
9
219
2
Order By: Relevance
“…This is an active research field and numerous beautiful examples have been described in the literature that has inspired this work. [191][192][193] …”
Section: Chapter 4 Multifunctional Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an active research field and numerous beautiful examples have been described in the literature that has inspired this work. [191][192][193] …”
Section: Chapter 4 Multifunctional Biomaterialsmentioning
confidence: 99%
“…206 Interestingly, an increase in cardiac cell electrical coupling through the gap junction proteins can be seen on the materials without external electrical stimulation. [191][192][193] …”
Section: Conductive Biomaterialsmentioning
confidence: 99%
“…19 The properties of this extracellular matrix-like architecture can be adjusted by incorporation of nanomaterials such as carbon nanotubes, nanowires, and nanoparticles. 20 For instance, You et al 21 developed an electrically conductive hybrid hydrogel scaffold based on gold nanoparticles homogeneously synthesized throughout a polymer template gel. The expression of connexin-43 increased in neonatal cardiomyocytes grown on the scaffold, suggesting that an electrically active scaffold impregnated with gold can enhance cardiomyocyte function.…”
Section: Applications Of Nanoengineered Scaffolds In Tissue Growth Anmentioning
confidence: 99%
“…The expression of connexin-43 increased in neonatal cardiomyocytes grown on the scaffold, suggesting that an electrically active scaffold impregnated with gold can enhance cardiomyocyte function. 21 Nanoscale topographical features (100 nm to 1 µm in size) defined on cell culture substrates can direct cell behavior, including polarity, migration, proliferation, and differentiation. For example, nanotopographical variations in the cell adhesion substrate can regulate differentiation of human mesenchymal stem cells towards adipocytes or osteocytes.…”
Section: Applications Of Nanoengineered Scaffolds In Tissue Growth Anmentioning
confidence: 99%
“…Auguste et al showed that spherical gold nanoparticles (AuNPs) could be synthesized in a HEMA-based scaffold, leading to an increase in conductivity of the materials. 12 Silicone field effective transistors embedded in Matrigel and synthetic scaffolds has also been shown to be conductive enough to enable real time monitoring of electrochemical signals from cardiomyocytes and neural cells. 13 Most of these systems, however ingenious, require complicated fabrication procedures and use of materials that are not yet approved for medical implants.…”
Section: Introductionmentioning
confidence: 99%